Sphingomonas sp. Hbc-6 alters physiological metabolism and recruits beneficial rhizosphere bacteria to improve plant growth and drought tolerance - Wang, Fang; Wei, Yali; Yan, Taozhe; Wang, Cuicui; Chao, Yinghui; Jia, Mingyue; An, Lizhe; Sheng, Hongmei (Frontiers in Plant Science, 2022)
Drought poses a serious threat to plant growth. Plant growth-promoting bacteria (PGPB) have great potential to improve plant nutrition, yield, and drought tolerance. Sphingomonas is an important microbiota genus that is extensively distributed in the plant or rhizosphere. However, the knowledge of its plant growth-promoting function in dry regions is extremely limited. In this study, we investigated the effects of PGPB Sphingomonas sp. Hbc-6 on maize under normal conditions and drought stress. We found that Hbc-6 increased the biomass of maize under normal conditions and drought stress. For instance, the root fresh weight and shoot dry weight of inoculated maize increased by 39.1% and 34.8% respectively compared with non-inoculated plant, while they increased by 61.3% and 96.3% respectively under drought conditions. Hbc-6 also promoted seed germination, maintained stomatal morphology and increased chlorophyll content so as to enhance photosynthesis of plants. Hbc-6 increased antioxidant enzyme (catalase, superoxide, peroxidase) activities and osmoregulation substances (proline, soluble sugar) and up-regulated the level of beneficial metabolites (resveratrol, etc.). Moreover, Hbc-6 reshaped the maize rhizosphere bacterial community, increased its richness and diversity, and made the rhizosphere bacterial community more complex to resist stress; Hbc-6 could also recruit more potentially rhizosphere beneficial bacteria which might promote plant growth together with Hbc-6 both under normal and drought stress. In short, Hbc-6 increased maize biomass and drought tolerance through the above ways. Our findings lay a foundation for exploring the complex mechanisms of interactions between Sphingomonas and plants, and it is important that Sphingomonas sp. Hbc-6 can be used as a potential biofertilizer in agricultural production, which will assist finding new solutions for improving the growth and yield of crops in arid areas.